Formulation and evaluation of cyclodextrin-based nanosponges of griseofulvin as pediatric oral liquid dosage form for enhancing bioavailability and masking bitter taste - Samia M. Omar; Fares Ibrahim; Aliaa Ismail (Elsevier, 2020)
The aim of this study was the development of griseofulvin (GRI) loaded β-cyclodextrin (β-CD) based nanosponges for bitter taste masking, improving dissolution rate and oral bioavailability. Plain NS (NS1 NS2 and NS3) were fabricated by reacting β-CD with the cross-linker diphenyl carbonate at different molar ratios (1:2, 1:4 and 1:6, respectively) using ultrasonication method. The NS2 provided both highest %yield and GRI solubilization enhancement. Thus, the drug was loaded in NS2 at different NS2: drug weight ratios in presence or absence of 0.25%w/w polyvinylpyrolidone (PVP k30). The GRI loaded NS (F1) that provided highest drug loading capacity and entrapment efficiency (47.20 ± 0.38%, 84.91 ± 0.30%, respectively) was morphologically examined using scanning electron microscopy (SEM). Also, Particle size, zeta potential, differential scanning calorimetry (DSC), Fourier transform infra-red (FT-IR), nuclear magnetic resonance (NMR) spectroscopy, in-vitro release, taste masking potential were evaluated. Moreover, in-vivo Pharmacokinetic studies were performed on rats. The F1 showed particle size 665.9 ± 13.8 nm and zeta potential −21.5 ± 0.7 mV. The DSC and FT-IR analysis confirmed the complexation of GRI with NS2. Nanosponges (F1) provided 3.19, folds increase in dissolution efficiency %, 2.13 and 3.78 folds increase in Cmax and AUC0-48 compared to plain GRI. Taste masking evaluation confirmed the potential of GRI nanosponges (F1) in masking the bitter taste of GRI completely. The study confirmed that complexation of GRI with NS would be a viable approach for masking the bitter taste of GRI and improving oral bioavailability, that Cmax, Tmax and AUC 0-48 were significantly higher for the developed formulation (F1). Keywords: Griseofulvin, Nanosponges, Cyclodextrin, Taste masking, Bioavailability